Numerical Investigation of the Influence of Different Suction and Discharge Ports on Scroll Expander Performance - Jian, Sun; Bin, Peng; Guo, Zhu B. (Recent Patents on Engineering, 2024)
Background: With the rapid consumption of non-renewable energy such as coal, oil and natural gas, the growing demand for environmental protection, the re-utilization of low-grade waste heat energy has become an important approach to improve energy utilization efficiency. As a new technology, organic Rankine cycle (ORC) power generation technology can make full use of and convert heat waste. Objective: Both the suction and discharge pressures of the scroll expander have a certain influence on the output and motion characteristics of the orbiting scroll. By studying the position and arrangement of the suction and discharge ports of the expander, a theoretical basis can be provided for the design of these ports. Methods: For the scroll expander using working fluid R134a, establishing the geometrical and three-dimensional models of the suction and discharge ports of the scroll expander with different positions and structures, based on the Computational Fluid Dynamics (CFD) method. Results/Discussion: Through comprehensive comparison, it was found that the structure of the original suction pipe outperformed any of the other structures; the fluid flow in the original discharge pipe was more complicated, and the simplified model of the commonly used scroll mechanical discharge pipe had the optimal performance. Conclusion: Compared with the original prototype SEI2, the suction port area is increased, and the suction port pulsation intensity coefficient and the suction pressure loss coefficient of the prototype SEI4 are reduced by 34.833% and 5.264% respectively, which can make the suction process of the expander more stable. Since the unilateral discharge ports Outlet3 and Outlet5 are located in the moving and static regions, respectively, there is a difference in the perturbation of the outlet fluid by the movable scroll, so that the gas pulsation intensity at Outlet3 is nearly double that of Outlet5.
Keywords: low-temperature waste heat utilization